VIBRATION REDUCTION OF NONLINEAR OBJECT WITH AN ADAPTIVE PROPORTIONAL-DERIVATIVE CONTROLLER WITH A MRAS STRUCTURE - Ostrowski, Mariusz; Jarzyna, Wojciech (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The paper presents a method of adapting the MFC actuator control algorithm used for nonlinear vibration reduction of an cantilever beam. The mathematical description presented of the PD controller operating in the MRAS structure and the adaptation algorithm is based on the Lyapunov principle. The simulation study carried out defines the algorithm’s resistance to modelling errors and hardware delays occurring in real systems.